Methodological Issues in Shadow Economy Estimation - E. V. Pecheritsa; D. M. Orobchenko (Управленческое консультирование)
The study covers an analysis of Rosstat’s methodology and data on Russia’s “shadow economy”. We explore potential shortcomings in the interpretation of three groups of indicators: adjustments for economic operations not observed by direct methods; unrecorded wage payments; employment in the informal sector and unregistered/undocumented employment. The economy unobserved by direct statistical methods and unregulated covers a significant part of the country’s economic life. The official statistical calculations of the American system of national accounts during the Great Depression reflect the need for adequate, complete, and harmonized estimates of shadow activities. Using archival data and microdata from Rosstat surveys, we show that discrepancies in revisions (vintages) of official estimates can lead to significant divergences, reaching tens of percentage points of GDP. The adjustments to gross value added used by Rosstat, without a synchronous analysis of national accounts, do not meet the goals of comparability and harmonization. Estimates of unrecorded wage payments are extremely limited in terms of explanatory and prognostic value. Finally, the estimates of informal employment proposed by the statistical agency virtually fully correspond to estimates of employment in the informal sector. The latter, in turn, do not reflect the nature of the shadow employment economy, as they rely on the production criterion. As we believe, the less popular in the literature estimates of undocumented employment and/or unregistered self-employment are more suitable for assessing the dynamics and structure of shadow practices in Russian employment. The use of such estimates is complicated by the closed nature of labor force survey materials. Thus, Rosstat holds non-public estimates of the number of employees whose employers evade taxes and contributions, as well as data on the number of self-employed individuals engaged in unregistered entrepreneurial activities, but does not publish this information. We emphasize the need to develop a unified approach to enhance the harmonization and comparability of both national and international statistics.